Functional Capacity Training for Improvement of VO2 Max in Football Players: Differences in The Effects of Circuit Training and Interval Training Models - Ummy Aisyah Nurhayati; Baiq Nurul Hasnawati (Universitas Pendidikan Indonesia, 2024)
Football players should be in good physical condition to support their performance on the pitch. For example, the cardiorespiratory capacity (VO2 max) needed to maintain endurance during the game. An increase in VO2 max indicates the ability of the heart and lungs to function optimally during exercise. Low endurance can cause football players to tire easily. Exercises that can be done to increase VO2 max are circuit training and interval training. Circuit training has a physiological effect on the muscles. They adapt and are automatically able to increase the maximum oxygen volume. Interval training has an effect on the metabolic waste produced by the muscles during rest, which increases oxygen consumption during exercise and increases VO2 max. The aim of this study was to determine the difference in the effect of circuit training and interval training on increasing VO2 max in football players. For the research method, an experimental method was used with a quasi-experimental approach to pre and post test two grub design treatment, the sampling technique used total sampling, a sample of 44 people with a 3x a week training programme for 6 weeks. The research instrument used was the multi-stage fitness test and the data analysis used was the paired samples t-test. Results showed that there was an effect of circuit and interval training on increasing VO2max in footballers (P=0.00 P0.05), with a more significant effect in the circuit group.